Congenital disorders of glycosylation presenting as epileptic encephalopathy with migrating partial seizures in infancy. (13th May 2016) - Barba, Carmen; Darra, Francesca; Cusmai, Raffaella; Procopio, Elena; Dionisi Vici, Carlo; Keldermans, Liesbeth; Vuillaumier‐Barrot, Sandrine; Lefeber, Dirk J; Guerrini, Renzo; ,
Abstract : Aim: Epilepsy is commonly observed in congenital disorders of glycosylation (CDG), but no distinctive electroclinical pattern has been recognized. We aimed at identifying a characteristic clinical presentation that might help targeted diagnostic work‐up. Method: Based on the initial observation of an index case with CDG and migrating partial seizures, we evaluated 16 additional children with CDG and analysed their clinical course, biochemical, genetic, electrographic, and imaging findings. Results: Four of 17 consecutively observed children with CDG (three females, one male) were first referred between the first and fourth month of life, after early onset of migrating partial seizures. All four patients manifested developmental delay, microcephaly, and multi‐organ involvement. Magnetic resonance imaging disclosed cerebral and cerebellar atrophy. Isoelectrofocusing of transferrin, enzymatic studies, and lipid‐linked oligosaccharide analysis indicated CDG‐I. Genetic testing demonstrated either homozygous or compound heterozygous variants involving the ALG3 gene in patients 1 and 3, the RFT1 gene in patient 2, and the ALG1 gene in patient 4. At last follow‐up, patients 1 and 2 were 5 and 3 1/2 years old. Patients 3 and 4 had died due to respiratory failure during pneumonia and refractory status epilepticus respectively. Interpretation: Children with migrating partial seizures and concomitant multisystem involvement should be investigated for CDG. What this paper adds: Infants with congenital disorders of glycosylation (CDG) may present with early onset migrating partial seizures. Migrating partial seizures in CDG are part of a complex clinical picture. Clinical presentation includes developmental delay, quadriparesis, microcephaly, and multi‐organ involvement. This article is commented on by Varadkar on pages1001–1002 of this issue.